Triglyceride level and soft drink consumption predict nonalcoholic fatty liver disease in nonobese male adolescents - Kado, Akira; Inoue, Yukiko; Moriya, Kyoji; Tsutsumi, Takeya; Ikeuchi, Kazuhiko; Okushin, Kazuya; Yotsuyanagi, Hiroshi; Koike, Kazuhiko; Fujishiro, Mitsuhiro (Hepatology research, 2023)
Aim Differential metabolic risk factors of nonalcoholic fatty liver disease (NAFLD) in nonobese male adolescents were analyzed examining relationships between NAFLD and clinical parameters of metabolic syndrome, including exercise and soft drink consumption, in male adolescents. Methods In total, 134 male university students (nonobese, n = 78; obese, n = 56) who underwent the first‐year health checkup were divided into the NAFLD and non‐NAFLD groups based on abdominal ultrasonography (AUS) findings. Relationships between NAFLD and metabolic parameters, including body mass index (BMI) and AUS score, were examined in nonobese students. Results Metabolic factors associated with hypertension, abdominal fat, liver damage, dyslipidemia, and impaired glucose tolerance were significantly less common in nonobese students than in obese students. The aforementioned factors and soft drink consumption were significantly more common in the NAFLD group than in the non‐NAFLD group. The univariate and multivariate analyses of nonobese students showed that the triglyceride level (odds ratio [OR], 1.06; 95% confidence interval [CI], 1.01–1.10, p = 0.001) was higher and soft drink consumption (OR, 36.8; 95% CI, 3.69–368, p < 0.001) was more common in the NAFLD group than the non‐NAFLD group. Conclusions Triglyceride level and soft drink consumption could aid in the detection of NAFLD in nonobese male adolescents. Our findings could provide useful information related to NAFLD and metabolic syndrome in nonobese adolescents. Nonobese and obese male adolescents might have differential backgrounds of nonalcoholic fatty liver disease (NAFLD), and we should separately examine these two clinical characteristics. Triglyceride blood level and soft drink consumption could be useful to detect NAFLD in nonobese male adolescents; therefore, inquiry about usual consumption of soft drinks is clinically important in addition to blood tests. Adolescents, especially nonobese male adolescents, should be careful of excessive soft drink consumption to prevent NAFLD.